The Influence Of Organizational Culture And Compensation On Employee Performance Through Job Satisfaction As Intervening Variables At Company X In Yogyakarta - Arifina, Salsa Husna; Setiawati, Trias; Palupi, Majang (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2024)
The goal of this research is to examine the relationship between organisational culture, compensation, and employee performance at Company X in Yogyakarta via the moderating effect of job satisfaction. In this quantitative study, questionnaires were sent online using Google Forms to collect data. Using a stratified random sample technique, we selected 94 employees from a population of 313. The t-test, the F-test, simple and multiple linear regression analysis, and path analysis all play roles in the study's analysis procedure. Employee performance is positively impacted by organisational culture and salary, which in turn positively impacts job happiness, which in turn positively impacts employee performance, as shown by this study. Studies reveal that the relationship between organisational culture and compensation and employee performance is complex, with job satisfaction variables acting as intermediaries. Organisations should dig deeper into the causes of pleasure because of the mediating function it appears to play.